Causes of mortality in a neonatal intensive care unit in Iran: one year data (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Neonatal mortality rate is a major health index. Approximately, 65% of all deaths in the first year of life occur during this 4-week period. The present study was conducted to investigate the mortality rates and causes of death in a neonatal intensive care unit (NICU) in Ahvaz, Iran in a year. METHODS This cross-sectional study was conducted in the NICU of Sina Hospital in Ahvaz. Medical records were studied, and data from 1,040 newborns admitted to the NICU within one year (March 2016 to March 2017) were collected following a checklist. Of these newborns, 123 died, and their relevant data were collected. Data were analyzed using SPSS, version 20 (SPSS Inc., USA). RESULTS The mortality rate was 11.82% (123 cases) out of 1,040 newborns admitted to NICU. Most of the newborns (48.8%) died on days 1–7. The causes of death were respiratory distress syndrome (RDS) (34.1%), asphyxia (25.2%), anomalies (10.6%), sepsis (7.3%), intracerebral hemorrhage (8.1%), pulmonary hemorrhage (7.3%), and other causes (6.4%), such as hydrops, severe pneumothorax, severe renal failure, and others. CONCLUSIONS The mortality rate in the NICU of this center was similar to that in other Iranian provinces. The most common causes of NICU mortality included prematurity and its complications, such as asphyxia and RDS. Thus, a strategic plan for reducing preterm delivery and asphyxia are necessary.